Effects of antibiotics on chicken gut microbiota: community alterations and pathogen identification - Zhan, Ruiqi; Lu, Yining; Xu, Yuan; Li, Xiaokun; Wang, Xilong; Yu, Guanliu (Frontiers in Microbiology, 2025)
The extensive use of antibiotics in animal husbandry, either for therapeutic purposes or as growth promoters, has raised significant concerns about their effects on poultry. However, when antibiotics are used as therapeutic agents, their impact on the gut microbiota of poultry remains unknown. This study aimed to address this gap by simulating therapeutic application of six frequently used antibiotics (lincomycin hydrochloride, gentamicin sulfate, florfenicol injection, benzylpenicillin potassium, ceftiofur sodium, and enrofloxacin infection) and investigated their effects on the composition and structure of poultry gut microbiota. Single-molecule real-time 16S rRNA sequencing was performed to analyze fecal samples collected from chickens treated with each antibiotic to assess the impact of antibiotic exposure on gut community diversity and dominant microbial species. Although the results demonstrated that antibiotic exposure reduced gut microbiota diversity and disrupted community stability, the impacts of different antibiotics differed considerably, specifically in the number of ASVs. Notably, the dominant bacterial phyla—Pseudomonadota and Bacillota—was largely consistent across different antibiotic exposures, except 11 days after gentamicin sulfate exposure. Moreover, six third-category pathogens were identified in fecal samples, namely, Shigella boydii, Escherichia coli, Shigella flexneri, Salmonella enterica, Corynebacterium bovis, Proteus mirabilis. Of these, three strains of Corynebacterium bovis were identified as potential novel pathogenic bacteria. These findings demonstrate the critical importance of rational antibiotics use in animal husbandry. This study provides a scientific basis for improving current antibiotics use in the treatment and prevention of poultry diseases, advancing the standardization and precision of antibiotic usage.